2004
DOI: 10.1097/01.smj.0000136284.79541.05
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Myocarditis Presenting with Wide Complex Tachycardia

Abstract: Fulminant myocarditis is an uncommon diagnosis characterized by cardiac failure preceded by symptoms of a viral illness. Presentation can frequently mimic acute myocardial infarction. The electrocardiographic changes are frequently nonspecific, but include ST segment elevation and T wave changes, as well as conduction abnormalities. We report the case of a patient with fulminant myocarditis that presented with sinus rhythm, a conduction system abnormality, and severe ST segment elevation mimicking ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Initial troponin levels in myocarditis within twelve hours of presentation of only as high as ∼ 50 ng/ml was reported in various published articles [8-15] with a wide range (< 1 to 48.5 and a mean of 12.25 ng/ml). The peak troponin level even in fulminant forms of myocarditis was reported to be less than 50 ng/ml in majority of published reports [4, 9, 11, 12, 14, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial troponin levels in myocarditis within twelve hours of presentation of only as high as ∼ 50 ng/ml was reported in various published articles [8-15] with a wide range (< 1 to 48.5 and a mean of 12.25 ng/ml). The peak troponin level even in fulminant forms of myocarditis was reported to be less than 50 ng/ml in majority of published reports [4, 9, 11, 12, 14, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Troponin I has limited sensitivity (34%) in the setting of acute myocarditis [7]. The degree of elevation of the cardiac markers in acute myocarditis is directly proportional to the degree of myocardial damage, i.e., less in focal compared to diffuse form [8] and more in fulminant than in non-fulminant cases [1]. For the same reason the degree of cardiac enzyme elevation is less in the initial stages of the disease and worsens during the clinical course with greater myocardial tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, studies have shown that the body can release large amounts of vasoactive peptides and catecholamine excitation-induced coronary artery spasm, while direct viral invasion can also result from coronary artery coronary in ammation, leading to in ammatory edema and aggravated myocyte ischemia following ischemia due to myocardial gap junction between change and the change of ion ow [21]. This can contribute to abnormal myocardial polarity, ECG ST-segment elevation, T wave inversion, QT interval prolongation, and ECG changes that may appear similar to those associated with acute myocardial infarction [22,23]. VA-ECMO support can reduce cardiac preload and cardiac oxygen consumption, allowing the heart to rest while correcting cardiogenic shock, increasing cardiac diastolic pressure, enhancing coronary perfusion, and alleviating myocardial damage resulting from hypoperfusion [2,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…22 Consequently, sudden cardiac arrest or ventricular arrhythmia has indeed been reported in the literature as the initial presentation of myocarditis, but only as a rare occurrence. [23][24][25][26][27] The autopsy findings in our case demonstrate an overwhelming systemic inflammatory process, as exhibited by massive infiltration of inflammatory cells in multiple organ systems, namely the heart, lungs, and skeletal muscle. This inflammatory process, by means of aggressive inflammatory myocarditis and specific involvement of the conduction system, triggered malignant ventricular arrhythmias that ultimately led to the patient's death.…”
Section: Discussionmentioning
confidence: 99%